(untitled) (ELang | An English Language Education Journal, 2018)
This paper entitled “the effectiveness of using miming game in teaching the present continuous tense” is written as partial fulfillment of the recruitments of sarjana pendidikan degree. The objective of this research is to know whether miming game is effective to improve the students’ mastery of present continuous tense and to know the students’ response to ward the method. This research is conducted to answer the question: Is the miming games technique effective to improve students’ mastery of present continuous tense? And What are the students’ response toward the use of miming game in learning present continuous tense? A pre- experimental research is applied as the research design in the first grade students of Mts Negeri 1 Bandung. The sample of this research is class H with the total 30 students as sample. The technique used to gain the data is tests, those are pre-test, and post-test, and also questionnaire. And the result of the value of t- that is 5.691 with the df = 29 at p = 0.05 of two tailed, the critical value of t-table is 2.045. As the value of the derived t- is higher than t-table (5.691 > 2.045) so that the Null Hypotheses (Ho) is rejected and the Alternative Hypotheses (Ha) is accepted meaning that there is significant difference in the result of students score before and after the treatment using miming game. This means that the use of miming game in teaching present continuous tense to the first grade of Mts Negeri 1 Bandung is effective. Furthermore, from the questionnaire, most of the students gave positive response toward the use of miming game in learning present continuous tense. This can be seen from the result of the questionnaire that miming game make them motivated in learning English especially present continuous tense. Key word : Game, Teaching, present continuous tense